Chronic persistent hepatitis: hepatitis B virus markers and histological follow-up. Issue 5 (May 1979) - Chadwick, R G; Galizzi, J; Heathcote, J; Lyssiotis, T; Cohen, B J; Scheuer, P J; Sherlock, S
Abstract : Twenty-six untreated patients with chronic persistent hepatitis were followed prospectively for one to 17 years (mean 5.6 years). The patients developed no clinical features of chronic liver disease. Raised serum transaminase levels were usually, but not consistently, the only biochemical abnormality; gamma globulin values were normal. Serum markers of past or present hepatitis B infection were found initially in 14 patients: another two developed markers during their follow-up. Nine patients progressed to a mild or moderate chronic active hepatitis as shown by serial needle liver biopsies but there was no evidence of cirrhosis. This progression was not associated with any clinical or biochemical deterioration. Seven of these patients had presented with insidious symptoms, seven had serum markers of hepatitis B infection, and the four who were HBsAg positive had relatively lower serum HBsAg concentrations than did those patients who continued with chronic persistent hepatitis.